Molecular tools and analytical approaches for the characterization of farm animal genetic diversity - Lenstra, J. A.; Groeneveld, L. F.; Eding, H.; Kantanen, J.; Williams, J. L.; Taberlet, P.; Nicolazzi, E. L.; Soelkner, J.; Simianer, H.; Ciani, E.; Garcia, J. F.; Bruford, M. W.; et al. (Wiley-Blackwell, 2012)
Genetic studies of livestock populations focus on questions of domestication, within- and among-breed diversity, breed history and adaptive variation. In this review, we describe the use of different molecular markers and methods for data analysis used to address these questions. There is a clear trend towards the use of single nucleotide polymorphisms and whole-genome sequence information, the application of Bayesian or Approximate Bayesian analysis and the use of adaptive next to neutral diversity to support decisions on conservation.
Keywords: adaptive variation; breed history; domestication; genetic diversity; livestock; population genetics; review